Efek Analgesik Ekstrak Etanolik Daun Mangrove Api-Api Putih (Avicennia alba) terhadap Mencit (Mus musculus L.) Jantan yang Diinduksi Asam Asetat 0,7% - ANDREW THEO WILLIAM CHRIS PURMATA; LESTARI DEWI; CHOESNAN EFFENDI (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Background : Avicennia alba or known as mangrove api-api putih is a type of mangrove species which has many benefits and often to be used by the local Indonesians as traditional medicine. The alcaloid and flavonoid substances derived from Avicennia alba leaves could inhibit pain. This study aims to determine the analgesic effect of Avicennia alba leaves extract in male mice (Mus musculus L.) induced by acetic acid 0,7%. Method :25 mice were divided into 5 groups that were given different therapies. The therapy are 10 mL/kg bw of water, 150 mg/kg bw of acetosal, 250 mg/kg bw; 500mg/kg bw; 1000 mg/kg bw of Avicennia alba leaves extract. 0,7% acetic acid with dose of 10 mL/kg bw is given to each subject intraperitoneally 30 minutes after the therapy to induce pain. The pain is manifested as writhes in mice, the writhes then are counted repeatedly each 10 minutes for 30 minutes. Result:: mean of writhes in group treated with Avicennia alba leaves extract in 250 mg/kg bw and 500 mg/kg bw with each value 6,20 and 9,40 are less than mean of writhes in negative control group with value 31,40. %inhibition of Avicennia alba leaves extract with dose of 250 mg/kg bw and 500 mg/kg bw respectively are 80,25% and 70,06%. Conclusion : Avicennia alba leaves extract in 250 mg/kg bw and 500 mg/kg bw dosage showed analgesic effect in male mice (Mus musculus L.) induced with 0,7% acetic acid.